KAJIAN LITERATUR PENGARUH TEKANAN DAN TEMPERATUR KEMPA SERTA JENIS ADHESIVE TERHADAP SIFAT FISIK DAN MEKANIK PARTICLEBOARD DARI LIMBAH SLUDGE INDUSTRI PULP DAN KERTAS - MEIYER MARTHEN KINDA; NINA TURNIP; CINDY SITORUS; PUTRA SIBUEA (LP2MTBM MAKARIOZ, 2020)
Wood is the material most widely used in human life. The high demand for wood requires an alternative that can replace thefunction of wood, especially in the particleboard industry. As a material that contains biomass, sludge waste from pulp andpaper industry has a great potential to be used as raw material for making particleboard. The use of sludge waste as rawmaterial for making particle boards can also reduce the impact of environmental pollution. In particleboard manufactures,additives are needed to improve the quality of particleboard. Additives used can be in the form of an adhesive or a matrix. Inthis literature study, we will review the effects of pressure, temperatur, and adhesive types on the physical and mechanicalproperties of the resulting particleboard. Physical properties to be reviewed in the form of water content, density, andthickness development, while mechanical properties to be reviewed in the form of modulus of elasticity (MoE), modulus ofrupture (MoR), and tensile strength. The physical and mechanical properties obtained will then be compared with SNI 03-2105-2006 which is the national standard for particleboard products. In this literature study, it was found that the optimumpressure and temperature ranges for the manufacture of particleboard are 30 kg/cm2 and 180oC respectively. Utilization ofbio-based adhesives such as citric acid and lignin is known to be able to produce particleboard that fulfill SNI 03-2105-2006standards so that it can be used to reduce the use of chemical-based adhesives.